L’habitat participatif : d’une greffe à un noyau des écoquartiers - Camille Devaux (Développement Durable et Territoires)
This article put into question inhabitants involvement in sustainable neighbourhoods from the example of cohousing. Even if the design of cohousing is independent of sustainable neighbourhood, institutional actors consider that it can be a tool. Cohousing is also transplanted and its characteristics aren’t necessarily totally in balance with those of sustainable neighbourhoods. Three points are particularly concerned : architectural conception, actors’ system and temporalities. So, to make cohousing a kernel of sustainable neighbourhoods, it has to be integrated from the beginning of the conception.